The Role of Infrastructure in Land-use Dynamics and Rice Production in Viet Nam - Christopher M. Edmonds (Asian Development Bank (ADB), 2002)
"This study examines the role of infrastructure development and technical change in explaining increases in agricultural production and changes in land use in the Mekong Delta Region of Viet Nam during the mid-1990s. The study relies on econometric analysis of household-level longitudinal farm survey data covering about 150 farms from eight villages in the Mekong River Delta from1994 to 1998. A model is developed that combines spatial factors in a neoclassical production framework to examine changes in land use and agricultural technology. Estimates make use of panel data estimation procedures that control for the effect of unobserved variables. Major findings emerging from the study are that the transportation costs involved in moving agricultural input and output between farms and markets significantly effect farm land use and production decisions. Greater transport costs reduced the likelihood that farms adopt intensive cropping patterns or cultivate nonrice crops. Improvements in roads and waterways both reduce transport costs in the area. Results suggest the quality of local water management infrastructure is much more important than transport costs in explaining the increased intensity of land use and level of production observed in the Mekong Delta during the 1990s. A simulation model is developed to highlight the implications of findings for policy aiming to increase rice production or alter land use in the Mekong Delta in the future. Unfortunately, lack of information on the costs of alternative infrastructure investments limits the policy conclusions that can be drawn from the study."
hdl:11540/1933
Keywords: 330; Reisanbau; Landnutzung; Ländliche Infrastruktur; Vietnam; Mekong